(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Fast food has long ceased to be just a convenient meal – it has become an integral part of modern consumer culture, especially among young people. This article provides an in-depth analysis of the impact of fast food on health, mental well-being, and social behavior among youth. The reasons for the popularity of fast food, its long-term consequences, and possible ways to minimize harm are examined. The article presents data from international studies and real cases of healthy eating programs implemented in different countries.